Forest Right Act and Climate Change Vulnerability: Impact on Forests and Forest Dwelling Communities in Maharashtra - Sharma, Jitendra Vir; Gokhle, Yogesh; Chauhan, Suresh; Tyagi, Aparna (Indian Forester, 2015)
The Forest Right Act, 2006 has been implemented by Maharashtra State and recognized 108112 (Individual, Community and Community Forest Resource Rights) consisting of 305561.9 ha of forest land in 22 districts till 31st July 2014. The forest rights recognized on 14668.96 hectare of forest land are against the provisions of Forest right Act, 2006 which causes emission of 113395 tonnes of CO2 in the atmosphere due to deforestation and loss of opportunity for Carbon sequestration at the rate of 9017 tonnes of CO2 per year, and also the loss of other Ecosystem Services.